Experimental Study on Inertia Coefficient of Fixed Vertical Cylinder Subjected to Short Crested Waves - Mohd Nordzi, Nur Amirah (IRC, 2016)
Short crested wave represents the wave in the real sea condition. In this study, the inertia coefficient of a vertical cylinder subjected to short crested waves was determined experimentally in a wave tank in Offshore Laboratory of Universiti Teknologi PETRONAS. The experiment was conducted by considering four different wave parameters pertaining to major offshore sites in Malaysian with two different diameters i.e. 16 mm and 48 mm of cylinders to simulate the tubular members of an offshore platform.